Filipino women's morale and mood their relationships with appraisal of and coping with the political instability in the Philippines - Guiao, Isabelita Z.
An exploratory, correlational nursing study was conducted to examine the relationships between negative appraisal of and coping with political instability and violence in the Philippines and socio-demographic characteristics, morale, and mood of 200 Filipino women. Negative impact of thirteen stressful political situations was scored with the Modified Bryce Life Events Inventory. Affective-focused and problem-focused coping were measured with the Modified Jalowiec Coping Scale. The Cantril Self-Anchoring Scale was used to measure morale as indicated by life satisfaction. The Beck Depression Inventory measured mood as indicated by depression scores. An open-ended socio-demographic questionnaire designed by the investigator obtained the socio-demographic data on the respondents.{{{{Stepwise multiple regression demonstrated significant findings: 1) positive relationship between annual individual income and morale; 2) positive relationship between educational achievement and morale; 3) negative ...
Thesis (Doctor of Philosophy in Nursing) -- University of Texas at Austin
Keywords: Women; Coping; Morale; Mood (Psychology).